2020
DOI: 10.1111/dom.14129
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D for treatment of non‐alcoholic fatty liver disease detected by transient elastography: A randomized, double‐blind, placebo‐controlled trial

Abstract: Aim: To evaluate the effects of vitamin D on transient elastography (TE, FibroScan) indices of liver steatosis (controlled attenuation parameter [CAP]) and fibrosis (liver stiffness measurement [LSM]) in adults with non-alcoholic fatty liver disease (NAFLD). Patients and Methods: In this randomized (2:1), double-blind, single-centre, 12-month trial, patients with NAFLD were treated with vitamin D (1000 IU/day) (n = 201) or a matching placebo (n = 110). Two co-primary outcomes were changes in CAP and LSM after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 44 publications
1
18
0
Order By: Relevance
“…Concomitantly, the hepatic concentrations of adiponectin alongside the antioxidants and anti‐inflammatory markers increased significantly, while leptin with the pro‐inflammatory and pro‐oxidative stress molecules diminished in the VD and OM groups than the PC group. Our results are aligned with many reports that have advocated the potential therapeutic values of VD 3 26–28,48–50 and omega‐3 oils 17,21–25 against MAFLD, plausibly by enhancing insulin sensitivity, reducing lipogenesis alongside antioxidative and anti‐inflammatory actions.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Concomitantly, the hepatic concentrations of adiponectin alongside the antioxidants and anti‐inflammatory markers increased significantly, while leptin with the pro‐inflammatory and pro‐oxidative stress molecules diminished in the VD and OM groups than the PC group. Our results are aligned with many reports that have advocated the potential therapeutic values of VD 3 26–28,48–50 and omega‐3 oils 17,21–25 against MAFLD, plausibly by enhancing insulin sensitivity, reducing lipogenesis alongside antioxidative and anti‐inflammatory actions.…”
Section: Discussionsupporting
confidence: 91%
“…In contrast, VD 3 therapy reduced obesity, enhanced insulin sensitivity, modulated hepatic lipid metabolizing molecules, and mitigated inflammation and oxidative stress 26–28 . Although VD 3 also attenuated liver steatosis, deregulations of adipokines, inflammation, and oxidative stress in MAFLD patients, 48–50 other randomized clinical trials (RCTs) failed to detect significant beneficial anti‐steatotic effects for the hormone 51,52 . On the other hand, omega‐3 oils also abated MAFLD in murine by lowering insulin resistance, lipogenesis, inflammation, oxidative stress, and apoptosis 17,21,22 .…”
Section: Discussionmentioning
confidence: 99%
“…A case–control study of 3023 subjects in a community in Nanjing, China, found that an elevated serum vitamin D level decreased the risk of NAFLD 81 . In a 12 month randomized controlled trial, low and moderate doses of vitamin D (1000 IU/day) reduced hepatic steatosis and fibrosis in NAFLD patients 82 . A meta‐analysis of 544 NAFLD subjects from 10 trials also showed that vitamin D supplementation improved glycaemic control and insulin resistance in NAFLD patients 83 .…”
Section: Discussionmentioning
confidence: 99%
“…Dasarathy et al found that a low vitamin D level can independently predict the severity of NAFLD [ 31 ]. Some clinical trials also demonstrated that vitamin D supplementation has therapeutic effects on patients with NAFLD, including a reduction in liver enzymes, weight, and BMI and an improvement in lipid profile, glycemic control, insulin resistance, and hepatic steatosis and fibrosis [ 32 , 33 , 34 , 35 ]. However, a few studies reported insignificant relationships between vitamin D status and histological severity of NAFLD [ 36 ].…”
Section: Discussionmentioning
confidence: 99%